The effect of addition sorbitol and Carboxy Methyl Cellulose (CMC) on the quality of biodegradable plastics from avocado seed starch - Lydia Margaretha; - Ratnawulan (Department of Physics – Universitas Negeri Padang UNP, 2020)
So far the plastics used are made of synthetic polymer materials that are difficult to decompose in nature and their availability is very limited. The use of synthetic plastics increases every year so that it has an impact in the form of environmental pollution. Therefore, the effort can be made to tackle plastic waste, namely by replacing the use of synthetic plastics with biodegradable plastics. Biodegradable plastics used are made from natural materials, for example, starch. The starch used in this study was avocado seeds. Determination of the quality of biodegradable plastics is based on the results of tensile tests, elongation tests, and biodegradation tests of biodegradable plastics. The steps involved in determining the optimum conditions for CMC with a variation of CMC used as much as 15%, 20%, 25% (w/w starch), the second stage is determining the optimum conditions for sorbitol with a variation of 20%, 30%, 40% (w/w starch), the third stage is mixing avocado seeds starch with sorbitol and CMC of 20% by weight of avocado starch. The optimum condition for CMC was obtained from the addition of 3 grams of avocado seed starch and 20% CMC of starch (w/w starch) with the resulting tensile strength value of 9,07 MPa and 21,39% elongation, while the optimum condition for sorbitol was obtained from the addition of 3 grams of avocado seed starch and sorbitol of 40% by weight of avocado starch with a tensile strength value of 7,79 MPa and 24,38% elongation while the highest tensile strength value from mixing sorbitol and CMC was obtained from the addition of sorbitol concentrations of 40% by weight of avocado starch and CMC 20% by weight of avocado seed starch, namely 3,79 MPa and elongation of 32,61%. Percent of lost plastic weight has increased day by day. The largest percentage loss of biodegradable plastic weight was obtained from the addition of sorbitol concentrations as much as 20% w/w starch and CMC 20% w/w starch, which was 91,67%. The biodegradable plastic made from avocado seed starch is almost completely biodegradable by the eighth day.